2018
DOI: 10.1002/ags3.12176
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for pancreatic cancer: Barriers and breakthroughs

Abstract: Immunotherapy is a rapidly growing field and represents a paradigm shift in the treatment of malignancies as it offers a new therapeutic approach beyond surgery, conventional chemotherapy, and radiation treatment. Targeting immune checkpoints, such as cytotoxic T‐lymphocyte‐associated antigen 4 and programmed death 1/programmed death ligand 1 has had immense clinical success resulting in sustained treatment response for a subset of patients with certain malignancies such as melanoma, non‐small‐cell lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 63 publications
(75 reference statements)
2
124
0
Order By: Relevance
“…The "cold" nature of these tumors, as well as the abundance and complexity of their TME, may explain the lack of effectiveness of conventional immunotherapy treatments. Thus, combinatorial strategies targeting the immune system (e.g., PD-L1) and molecular inductors of pancreatic TME complexity (e.g., colony stimulating factor receptor 1(CSFR1), chemokine C-X-C receptor 4 (CXCR4)) are in clinical trials, and it is expected that the reprograming of the TME will improve the benefit of classical immunotherapy treatment [41].…”
Section: Targeting Mutant Kras-driven Effects That Shape the Cancer-imentioning
confidence: 99%
“…The "cold" nature of these tumors, as well as the abundance and complexity of their TME, may explain the lack of effectiveness of conventional immunotherapy treatments. Thus, combinatorial strategies targeting the immune system (e.g., PD-L1) and molecular inductors of pancreatic TME complexity (e.g., colony stimulating factor receptor 1(CSFR1), chemokine C-X-C receptor 4 (CXCR4)) are in clinical trials, and it is expected that the reprograming of the TME will improve the benefit of classical immunotherapy treatment [41].…”
Section: Targeting Mutant Kras-driven Effects That Shape the Cancer-imentioning
confidence: 99%
“…Recently it was shown that chronic administration of plerixafor is a feasible strategy for long‐term treatment of WHIM patients, reducing infection frequency and wart burden associated with the disease 17 . Chronic treatment with plerixafor is also being considered for additional clinical applications including pulmonary fibrosis, pancreatic cancer (Camplex‐1 trial), and leukemia, where the mechanism of action appears independent of the effect of plerixafor on neutrophil dynamics 18–20 . However if plerixafor affects neutrophil dynamics in the lung, it has the potential to compromise lung host defense and this may have a detrimental impact on these patients especially if otherwise immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“…Focal adhesion kinase activity drives induction of an immunosuppressive TME Analyses of patient pancreatic tumor tissue have shown that T cells can infiltrate pancreatic lesions and furthermore, in line with observations made in other cancer types, T cell infiltration also correlates with response to checkpoint blockade therapy in pancreatic ductal adenocarcinoma (PDAC; Torphy et al, 2018). Previous studies using GEMMs to model PDAC have characterized the resulting tumors as containing densely fibrotic stroma and immunosuppressive immune cell populations, namely, tumor-associated macrophages (TAM), MDSC, and Treg cells (Clark et al, 2007;Feig et al, 2012;Jiang et al, 2016).…”
Section: Recruitment Of Immunosuppressive Populationsmentioning
confidence: 62%